Perancangan Program Database Excel dengan Input Barcode Scanner di PT. Sat Nusapersada Tbk. - Nimatul Mamuriyah; Lina Lina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
PT Sat Nusapersada Tbk is a company engaged in the electronics industry and assembly. Sony Coin Battery is one of the departments that produce and package batteries which are then sold abroad. New materials or materials have their own barcode contained in each battery pack which needs to be scanned so that there are no errors in the delivery of goods from the store to the production department. So far, the existing database program is a database program with manual input without a barcode scanner. To meet the needs of scanning this new battery model, an excel database program was created with input in the form of a barcode scanner. To design a database store program equipped with a barcode scanner requires three stages. The three stages are data collection of the parts of the program, design of the program display form and coding design according to the function of each part. The designed program consists of three important parts, namely Incoming, Production and Shipment. These three sections are recorded in the excel database according to the battery model being run. The way it works is to scan the barcode then the data that has been typed and the barcode number will automatically enter the database. From the test results of the program, it was found that the program error rate was 4%. However, this program can be implemented to meet existing needs.